The Abbasid Rooting of the Caliphate Issue Through the Writings of Al-Jahiz - Hafidh Numa, Researcher. Mithaq; Abdulrazaq Hassan, Prof. Dr. Zachia (Basra studies journal, 2024)
This research, entitled "The Abbasid Justification of the Caliphate Issue Through the Writings of Al-Jahiz," examines what Al-Jahiz wrote in his works with the aim of providing significant service to the Abbasid state. He aimed to be one of its advocates and defenders against its adversaries by proving the legitimacy of the Abbasids’ claim to the caliphate. This required delving into the issue of inheritance, praising them, extolling their virtues, and spreading them among the people. Al-Jahiz relied on narrations and noble Prophetic traditions, employing them in this task to gain favor with the authorities. This occurred amidst the diversity of ideas and opinions, as well as the political fluctuations of Al-Jahiz’s era. In this research, an analytical approach is followed by referring to Al-Jahiz’s writings and other contemporary and subsequent sources.